2010
DOI: 10.1111/j.1095-8649.2010.02614.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discharge and local density on the growth of juvenile Atlantic salmon Salmo salar

Abstract: The study explored the combined effects of density, physical habitat and different discharge levels on the growth of juvenile Atlantic salmon Salmo salar in artificial streams, by manipulating flow during both summer and winter conditions. Growth was high during all four summer trials and increased linearly with discharge and mean velocity. Differences in fish densities (fish m(-3)) due to differences in stream volume explained a similar proportion of the variation in mean growth among discharge treatments. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 63 publications
0
25
1
Order By: Relevance
“…A reduced summer flow constrains fish in a restricted habitat, where fish compete for the most profitable position. Teichert et al (2010) manipulated flow and juvenile Atlantic salmon in artificial streams and demonstrated a similar positive relationship between growth and discharge (or mean velocity) during the summer. Juvenile brown trout generally display a drift-feeding behaviour (Glova & Field-Dodgson 1995).…”
Section: Discussionmentioning
confidence: 85%
“…A reduced summer flow constrains fish in a restricted habitat, where fish compete for the most profitable position. Teichert et al (2010) manipulated flow and juvenile Atlantic salmon in artificial streams and demonstrated a similar positive relationship between growth and discharge (or mean velocity) during the summer. Juvenile brown trout generally display a drift-feeding behaviour (Glova & Field-Dodgson 1995).…”
Section: Discussionmentioning
confidence: 85%
“…This approach has been criticized because such models almost exclusively address physical habitat characteristics, thus omitting potentially important biotic factors (Armstrong et al, 2003;Rosenfeld, 2003;Teichert et al, 2010) and because the relationships fit poorly when transferred across different river morphologies (Armstrong et al, 2003). Wisz et al (2013) reported that one solution to account for interspecific interactions is to use species distribution models in concert with biotic surrogate variables that reflect spatial turnover or gradients in the distribution of biotic interactions.…”
mentioning
confidence: 99%
“…This may have been caused by using a growth function parameterized from data from another river using only temperature as a predictor. Although growth is strongly related to temperature, other factors such as density of conspecifics (Teichert, Kvingedal, Forseth, Ugedal, & Finstad, ) and food availability (Arnekleiv, Finstad, & Ronning, ) may affect growth. These properties will likely have differed between the river where the model was calibrated and the River Mandalselva.…”
Section: Discussionmentioning
confidence: 99%